Moving towards routine evaluation of quality of inpatient pediatric care in Kenya. - David Gathara; Rachael Nyamai; Fred Were; Wycliffe Mogoa; Jamlick Karumbi; Elesban Kihuba; Stephen Mwinga; Jalemba Aluvaala; Mercy Mulaku; Rose Kosgei; Jim Todd; Elizabeth Allen; et al. (PLoS ONE)
Background Regular assessment of quality of care allows monitoring of progress towards system goals and identifies gaps that need to be addressed to promote better outcomes. We report efforts to initiate routine assessments in a low-income country in partnership with government. Methods A cross-sectional survey undertaken in 22 'internship training' hospitals across Kenya that examined availability of essential resources and process of care based on review of 60 case-records per site focusing on the common childhood illnesses (pneumonia, malaria, diarrhea/dehydration, malnutrition and meningitis). Results Availability of essential resources was 75% (45/61 items) or more in 8/22 hospitals. A total of 1298 (range 54-61) case records were reviewed. HIV testing remained suboptimal at 12% (95% CI 7-19). A routinely introduced structured pediatric admission record form improved documentation of core admission symptoms and signs (median score for signs 22/22 and 8/22 when form used and not used respectively). Correctness of penicillin and gentamicin dosing was above 85% but correctness of prescribed intravenous fluid or oral feed volumes for severe dehydration and malnutrition were 54% and 25% respectively. Introduction of Zinc for diarrhea has been relatively successful (66% cases) but use of artesunate for malaria remained rare. Exploratory analysis suggests considerable variability of the quality of care across hospitals. Conclusion Quality of pediatric care in Kenya has improved but can improve further. The approach to monitoring described in this survey seems feasible and provides an opportunity for routine assessments across a large number of hospitals as part of national efforts to sustain improvement. Understanding variability across hospitals may help target improvement efforts.